Social Conformity in Immersive Virtual Environments - Kyrlitsias, Christos (Department of Multimedia and Graphic Arts, Faculty of Fine and Applied Arts, Cyprus University of Technology, 2021)
In our daily lives, our decisions are greatly influenced by others. Conformity, one of the most powerful forms of social influence, is the act of matching attitudes, beliefs, and behaviors to group norms. It is an indirect social influence that is caused by the desire of the individual to either “fit in” the group, avoid rejection in the case of normative conformity, or be correct, in the case of informational conformity. Due to the recent advances in immersive virtual reality (IVR) and other related technologies, we are not only interacting socially with physical/real humans but also through technology with virtual humans (VHs). The related literature suggests that interaction with VHs can replicate the effects of human-human interactions. However, regarding conformity in immersive virtual environments (IVEs), the literature is limited. This thesis presents the investigation normative and informational conformity with VHs within IVEs using three experiments. In our first, experiment, we replicated the original Asch (1951) experiment within an IVE. The participants, immersed in a virtual room, were asked to state their judgments in a series of simple perceptual tasks (trials) either alone, or in the presence of five virtual confederates. In the latter condition, the confederates stated their estimates before the participant and were implemented programmatically to give a unanimous wrong judgment in some trials. The results showed that participants did not conform to the wrong confederates’ judgments and responded correctly to the trials. However, an influence on the participants’ response time by the virtual confederates’ judgments was observed, indicating that some degree of social pressure was exerted on the participants. These results led us to conduct a second experiment in order to further investigate the social pressure from VHs within IVEs. In the second experiment, additionally, we examined the impact of agency (i.e. the extent to which the user believes that a VH represents an avatar rather than an agent) and the virtual confederates’ behavioral realism. The results showed that normative conformity can be caused by VHs in IVEs, as participants responses were at some degree distorted by the false VHs’ answers. However, no effect of agency and behavioral realism was observed, even if participants in the high behavioral realism condition reported a stronger sense of social presence (the sense of being together with others). In our third experiment we focused on informational conformity. This was done by increasing the difficulty of the task in relation to the previous experiments by limiting the stimuli projection duration. Additionally, we investigated the impact of social presence of informational conformity using two levels of virtual confederates’ behavioral realism (and specifically gaze behavior), as in the second experiment. The results showed that participants conformed with the virtual confederates, as the participants gave significantly more incorrect responses to the trials in which the confederates also gave an incorrect response, compared to those trials in which the confederates gave correct answers. Participants in the high behavioral realism condition reported stronger social presence than participants in the low behavioral realism condition. However, no difference in the level of conformity was observed between the two conditions, showing no impact of social presence on conformity. Additional results based on self-reported measures showed a number of social effects that occurred only in the high behavioral realism condition, such as participants’ confidence, indicating that social presence has an impact on the participants’ experience. The outcomes of this research extended the existing literature with additional knowledge. We provided empirical evidence that a group of VHs can influence the user’s decision making within IVEs through informational (to a greater extent) and normative (to a lesser extent) conformity. The implications of this study on the use of VHs in immersive applications as well as future research directions are also discussed within this dissertation.
Keywords: Virtual reality; Conformity; Virtual humans; Behavioral realism; Agency; Social presence